A study on self-curing self-compacting concrete filled steel columns subjected to axial compression. (2022) - Beulah Gnana Ananthi, G.; Sivakumar, N.
Abstract: For vehicle parking areas, in multi-storey buildings and bridge piers, composite tubular columns have been considered as a better solution. The cold-formed steel and concrete combination is notable, because of the benefits of inherent material properties of both the materials. Concrete filled tubular (CFT) columns is in-filled with concrete having single tubes or concentric double tubes leaving the core as hollow. Moreover, for the design of such composite columns a specific design code is yet to be released in India. Henceforth, this experimental research intends to study the structural behaviour of CFT columns, consisting steel tube in terms of load- deflection graph, ultimate load carrying capacity, confinement of concrete and ductility. The structural use of a unique Self-Curing and Self-Compacting Concrete (SCSCC) using 10% granite saw dust waste and 25% fly ash as partial replacement to cement was confirmed. The experimental results are compared with computer modelling analysis done using ABAQUS for a better understanding of the column specimen's behaviour. Based on experimental studies percentage of super plasticizer and Super Absorbent Polymer (SAP) is determined as 1.3% & 0.3% respectively. The variation between experimental and analytical results is minimum and is due to minor material defects in steel sections. In this present experimental study three different cross sections namely: (i) cylindrical (ii) rectangular and (iii) square cross sections with 500 mm length and 2 mm thickness was used. Secondly a parametric study was conducted for 3 different lengths and 3 thickness which also showed that the performance of square cross sections was effective irrespective of the lengths. The load carrying capability of columns with increased steel section thickness is seen to be greater for the same length of column. When compared to cylindrical sections, rectangular and square sections show a significant reduction in load carrying capability as the thickness of the steel section is reduced. These changes in load carrying capacity are mainly due to the shape factor. The main advantage of the CFST column is that it has a better ultimate strength than a regular column due to the concrete confinement. This increased strength due to confinement is higher in cylindrical specimens.